The Potency of Local Beef Cattle: Growth Performance, Carcase Productivity, and Beef Quality - Priyanto, Rudy; Hafid, Harapin (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
In the era of globalization, domestic beef supply from local cattle should meet not only the specification of traditional market but also that of modern markets which require premium beef. The local beef cattle consist of various breeds differing in maturity size, growth performance and slaughter weight. Small to medium frame size cattle are still dominant (±70%) and they are descendants of Bos javanicus, Bos indicus (draft type) and their crosses. The local cattle have relatively poor growth performances and slaughter weights. The carcass evaluation study suggests that taurus-indicus cross cattle tend to combine the muscularity advantages of taurus and indicus cattle which result in better beef yield and economic value. Therefore, the development of local cattle should be towards a beef type animal by cross breeding with larger frame taurine beef cattle. Since most of the cattle breeds contain Bos indicus blood, they yield relatively tough beef. Nevertheless, Bali cattle aged 1.5–2.5 years could produce relatively tender beef that meets specification of modern market. The program to improve the beef quality of Bali cattle could increase self-sufficiency in premium beef supply, added value and competitiveness of the local cattle. Keywords: local cattle, growth performance, beef yield, quality